2023
DOI: 10.1177/00368504231156297
|View full text |Cite
|
Sign up to set email alerts
|

Craniofacial characteristics in Crouzon's syndrome: A systematic review and meta-analysis

Abstract: The purpose of this meta-analysis was to strengthen the credibility of primary research results by combining open-source scientific material, namely a comparison of craniofacial features (Cfc) between Crouzon's syndrome (CS) patients and non-CS populations. All articles published up to October 7, 2021, were included in the search of PubMed, Google Scholar, Scopus, Medline, and Web of Science. The PRISMA guidelines were followed to conduct this study. PECO framework was applied in the following ways: Those who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The disease is characterised by the premature fusion of the coronal and sagittal sutures, which develop within the first year of life. Once the sutures are closed, further development is compromised, leading to midfacial hypoplasia, a shallow orbit and maxillary hypoplasia 6. Intraoral features consist of mandibular prognathism, oligodontia, overcrowding of the upper teeth, macrodontia, cleft lip and palate, peg teeth, widely spaced teeth, V-shaped maxillary dental arch and occasional upper airway obstruction 5 7.…”
Section: Descriptionmentioning
confidence: 99%
“…The disease is characterised by the premature fusion of the coronal and sagittal sutures, which develop within the first year of life. Once the sutures are closed, further development is compromised, leading to midfacial hypoplasia, a shallow orbit and maxillary hypoplasia 6. Intraoral features consist of mandibular prognathism, oligodontia, overcrowding of the upper teeth, macrodontia, cleft lip and palate, peg teeth, widely spaced teeth, V-shaped maxillary dental arch and occasional upper airway obstruction 5 7.…”
Section: Descriptionmentioning
confidence: 99%
“…Lu et al 5 revealed that Crouzon was characterized by a shortened anteroposterior maxillary length and posteriorly shifted mandible compared with healthy controls. Forte et al 6 noted that the nasion-sella pterygomaxillary fissure angle was more obtuse in Alam et al 7 and concluded that Crouzon syndrome is prone to have a retrusive maxilla, shorter and flatter cranial bases, and smaller orbital and mandibular volumes compared to the general population by meta-analysis.…”
mentioning
confidence: 99%